2018
DOI: 10.1055/s-0038-1667379
|View full text |Cite
|
Sign up to set email alerts
|

Side Effects of Phototherapy on Neonates

Abstract: Phototherapy in neonates for treatment of pathological jaundice is an effective therapeutic tool that is widely used in neonatal units. Over the past years, a greater concern has emerged about the effects on the immune and inflammatory system and its potential genotoxic and side effects, especially the late ones, possibly associated with childhood diseases, showing that this treatment is not as harmless as previously believed. Numerous studies assessing these possible adverse effects of phototherapy on neonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Thus, our data suggested that LR has the potential to affect the polarity and identity of NSC during early human neural development. These results may be of clinical relevance, since aggressive PT is used on preterm ELBW neonates, often accompanied by serious adverse effects [10,11]. It is also well known that the processes of neurogenesis and neurodevelopment are impaired in these neonates [51], which may even be exacerbated by BR photo-oxidation products generated during PT, based on our current data.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Thus, our data suggested that LR has the potential to affect the polarity and identity of NSC during early human neural development. These results may be of clinical relevance, since aggressive PT is used on preterm ELBW neonates, often accompanied by serious adverse effects [10,11]. It is also well known that the processes of neurogenesis and neurodevelopment are impaired in these neonates [51], which may even be exacerbated by BR photo-oxidation products generated during PT, based on our current data.…”
Section: Discussionsupporting
confidence: 72%
“…Although PT is considered the gold standard treatment for severely jaundiced neonates, there is a surprising lack of scientific data on the biological effects of bilirubin photo-oxidation products generated during PT. Importantly, PT does not seem to be entirely safe, particularly in ELBW preterm neonates [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phototherapy can change the structure of bilirubin and increase its excretion. This is currently the standard treatment for jaundice (3). The phototherapy device can have shortand long-term side effects for the baby one of which is damage to the microbial flora of the intestine.…”
Section: Introductionmentioning
confidence: 99%
“…Phototherapy is the most used and most scientifically proven treatment in neonatal jaundice, with several means of accomplishment. However, it is not a controversial technique, since it has a high cost, can cause side effects and creates a distance between the mother and the baby 44 . On average, in physiological jaundice, the phototherapy time is 3.9 days 45 , and there is a constant search for a reduction in that time.…”
Section: (Citation Of the Review Articles) Corroborating What Is Already Recommended By The Americanmentioning
confidence: 99%